2011
DOI: 10.1016/j.aorn.2010.09.029
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of a Holistic Approach During the Perioperative Period

Abstract: Holism is the philosophy of understanding people by addressing factors that affect people in all situations. The goal of holistic nursing is to help patients integrate appropriate self-care into their lives. By providing holistic care, the perioperative nurse can help surgical patients experience fewer problems (eg, surgical trauma, pain, anesthetic complications), reach discharge more quickly, attain satisfaction with health care, and more easily resume normal activities. Holistic nursing may include the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 18 publications
0
40
0
4
Order By: Relevance
“…Takase et al (2015) reported that holistic care was associated with better evaluations of the patients, prevention of over-looking the problems with potentially significant consequences, self-and job-satisfaction, protection of patient rights, increased and satisfactory collaboration with the whole healthcare team, and decreased rate of turnover in the nursing staff. Selimen & Andsoy (2011) stated that the patients and their families considered the holistic point of view during the provision of health care as a factor that improved health care. Thompson et al (2008) reported that holistic practices assisted the patients in adjusting to the illness.…”
Section: Introductionmentioning
confidence: 99%
“…Takase et al (2015) reported that holistic care was associated with better evaluations of the patients, prevention of over-looking the problems with potentially significant consequences, self-and job-satisfaction, protection of patient rights, increased and satisfactory collaboration with the whole healthcare team, and decreased rate of turnover in the nursing staff. Selimen & Andsoy (2011) stated that the patients and their families considered the holistic point of view during the provision of health care as a factor that improved health care. Thompson et al (2008) reported that holistic practices assisted the patients in adjusting to the illness.…”
Section: Introductionmentioning
confidence: 99%
“…A holistic approach encourages nurses to address all the physical, mental, emotional, spiritual and social needs of the patient by providing a complete model of care [1]. Meanwhile, spiritual needs are the deepest needs of the individual, and if nurses spend more time dealing with the spiritual issues of the patients, they will help resolve the psychological and physical problems of the patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…This sense of belonging and responsibility causes great impacts on egoistic tendencies and on hierarchical and coercive human relations of being. 21,18 By reporting to us the capacity of the human being to seek out resources of innate healing, the potential of the therapeutic touch as an instrument that instigates its practitioners to build their own state of equilibrium is perceived. The "new and emergent" in this research emerges from the moment that the participants expressed feeling more capable of "controlling stressful situations of life" and "planning better in the face of daily conflicts", being in the family and/or work environment.…”
Section: Once or Twice I Felt A Tingle (S2)mentioning
confidence: 99%